Factors influencing facebook usage for life happiness enhancement - Attan, Sri Azra; Bolong, Jusang (Human Resource Management Academic Research Society, 2022)
Why is our life happier when using Facebook? Have we ever realized that interpersonal attraction is important for us to be happier in SNS? That is the reason this paper needs to examine the factors influencing Facebook usage for life happiness enhancement. This study was using an integrated purposive sampling method through a snowballing procedure by respecting the characteristics of respondents to suit the purpose of the study. A total of 402 questionnaires were distributed online. The findings of this study formulated that physical attraction, social attraction, popularity, and extraversion contributed to life happiness enhancement. This means that happiness in life is not only can be obtained through Face-to-Face social interaction but life happiness can also be achieved through social media mediated-communication. Future research should investigate the effect on the different contexts of media communication through an alternative continuum of social media.